PSYCHOEDUCATIONAL FILM SERIES BASED ON PREMATURE MARRIAGE PREVENTION ON MENTAL HEALTH PREVENTION IN ADOLESCENT GIRLS - Wati, Erna; Alfianto, Ahmad Guntur; Ulfa, Miftakhul (Journal of Maternity Care and Reproductive Health, 2024)
Early marriages for teenagers can affect mental health, such as anxiety and stress in women. It's because of the emotional maturity of a teenager who's still developing. There needs to be psychotherapy, which includes health knowledge, life skills training, and empowerment. Psycho-education is an attempt to promote health through knowledge and skills. A film is a health promotion medium that influences those who watch it. Objective: Analyzing the effectiveness of early marriage-based psycho-educational health promotion media on the mental health of teenage girls. Methods: This study uses a quantum-experimental design. The study population consisted of 76 teenage girls. The sample in this study was 42 teenage girls aged 13–16. Sampling techniques use purposive sampling. A measure of the Mental Health Inventory questionnaire. The research was conducted between October 2023 and February 2024. Data analysis using SPSS 16 with paired t tests and independent t tests The research has also obtained ethical approval from the ethical committee of the Brahmanda Lentera Chakra Institute under ethical number No. 117/011/VIII/EC/KEP/LCBL/2023.Results: Analisis Paired t test didapatkan hasil 0,000 (<0,05). t independent test nilai rata-rata hasil post test kelompok intervensi yang diberi film sebesar 44,71 dan kelompok post test yang diberi leaflet sebesar 39,09 lebih kecil dibandingkan dengan nilai rata-rata nilai post test kelompok intervensi yang diberi film.  There are significant differences between the intervention groups given psycho-educational films and the groups given leaflet education. There are differences in the average values before and after the film intervention, and there is a difference between the average intervention group and the control group.